NITROGEN DYNAMICS ON RICE FIELD SOILS - MULYANI, NANAN S; SURYADI, M.E; DWININGSIH, S.; HARYANTO, . (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2001)
Nitrogen fertilizer is unstable, and it is predicted that large amount of it is lost through run-off, volatilization, and leaching processes. Information of nitrogen movement is needed in order to increase the efficient use of fertilizer, so that the N dosage and time of fertilizer application could be given precisely. Nitrogen movement through volatilization and from standing water and leaching could be observed by means of laboratory study using plastic pot which has been especially designed, and soil samples was taken after 1, 4, 7, 14 and 28 days of incubation. The green house experiment was held using IR-64 rice variety to see the sorption of nitrogen. The movement of nitrogen in standing water of Entisols until da showed that the concentration of NH4-N was higher than NO3-N, and afterwards NO3-N was higher than NH4-N. NH4-N concentration on Inceptisols until days-28 was higher than NO3-N. However, the NH4-N concentration on Vertisols until days- 28 was lower than NO3-N. The movement of nitrogen on Entisols and Inceptisols showed that the NH4-N concentration until days-28 was higher than NO3-N, however the NH4-N concentration on Vertisols until days-7 was lower than NO3-N. Nitrogen losses from fertilizer in standing water of Vertisols was found 31,7% at days-1 and 28,8% at days-4. The N uptake by crop was found the highest on Inceptisols (78,0%) and the lowest on Entisols (17,2%).